2021
DOI: 10.1016/j.resinv.2021.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Side effects and antibody titer transition of the BNT162b2 messenger ribonucleic acid coronavirus disease 2019 vaccine in Japan

Abstract: Background The coronavirus disease (COVID-19) has afflicted large populations worldwide. Although vaccines aroused great expectations, their side effects on Japanese people and the antibody titer transition after vaccination are unclear. Methods The side effects of the BNT162b2 mRNA COVID-19 vaccine in participants who received vaccination at our center were investigated. Some participants were also surveyed for the antibody titer transition. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 12 publications
10
24
0
Order By: Relevance
“…In this study, the female gender was also associated with development of moderate and severe post-vaccinal adverse effects, showing a positive correlation of gender to the severity of the post-vaccinal side effects. This finding also agrees with other findings and confirms that the development of post-vaccinal side effects were significantly higher in females than in males (23,24,29). However, it disagrees with a recent study (30) that reported that males TABLE 4 | Comparison between the post vaccine adverse effects after vaccination with BNT162b2 and ChAdOx1 as well as those after the first and the second doses of BNT162b2.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, the female gender was also associated with development of moderate and severe post-vaccinal adverse effects, showing a positive correlation of gender to the severity of the post-vaccinal side effects. This finding also agrees with other findings and confirms that the development of post-vaccinal side effects were significantly higher in females than in males (23,24,29). However, it disagrees with a recent study (30) that reported that males TABLE 4 | Comparison between the post vaccine adverse effects after vaccination with BNT162b2 and ChAdOx1 as well as those after the first and the second doses of BNT162b2.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, we did not include specific questions about anaphylaxis or myocarditis in the questionnaire. However, this study is relatively large compared to previous studies conducted in Japan [ 6 , 7 ] and is the first study in Japan to compare the adverse reactions to the two mRNA-based vaccines.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, continued monitoring of adverse reactions to COVID-19 vaccines under programmatic conditions, especially in young age groups, may provide relevant information to the public and contribute to people's acceptance of COVID-19 vaccines. However, programmatic evidence on the reactogenicity of COVID-19 vaccines in the Japanese population is limited [ 6 , 7 ]. In addition, there is a lack of evidence on the comparative side effects of different COVID-19 vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…The vaccine helps to prevent not only the onset [ 1 ] but also the progression of COVID-19. However, some people hesitate in getting vaccinated due to fear of relatively common adverse effects that occur shortly after vaccination with the BNT162b2 vaccine [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%